Multiproduct firms, consumer search, and demand heterogeneity - Yuta Kittaka (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This study constructs a sequential consumer search model with differentiated products in which some consumers search for a single product while the others search for multiple products. When the mass of consumers who demand one of the products decreases, the price for one product decreases while another price increases due to the joint-search effect, even if the products are neither complements nor substitutes. In addition, under some conditions, this decrease in demand causes an increase in each firm's profit.
Keywords: D11; D43; D83; L13; 330; consumer search; multiproduct pricing; demand heterogeneity